POLA KERJASAMA GURU DAN ORANG TUA DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA KELAS VII C SELAMA MASA PANDEMI COVID-19 DI MTS PAB 1 HELVETIA - Syahrul Sitorus; Delvi Andriadi; Syarah Juwita; Wahyu Dian Nasution (Prodi PAI Sekolah Tinggi Agama Islam Serdang Lubuk Pakam, 2020)
This study aims to analyze: (1) the pattern of cooperation between teachers and parents in improving students 'religious character, (2) supporting factors for teachers' efforts in improving students 'religious character, (3) inhibiting factors in improving students' religious character. This study uses a qualitative method with a descriptive phenomenology approach. The results of this study indicate that finding the communication patterns of teachers and parents is carried out with secondary communication patterns or two-way or reciprocal communication patterns (Two way traffic communication). Besides, this study also found two things, namely supporting factors and inhibiting factors that affect the cooperation of teachers and parents. Supporting factors consist of: 1) Awareness of the teacher's responsibility in teaching students, 2) Awareness of the responsibility of parents in giving and guiding their children to have a religious character, (3) a strong willingness of students to learn and change be better, (4) Between teachers and parents have attention and time to communicate, (5) Between teachers and parents of students get online media that is easy and comfortable to communicate, (6) A harmonious relationship between teachers, parents and pupils. While the inhibiting factors consist of (1) Lack of awareness of the teacher's responsibility (2) Lack of awareness of the responsibilities of parents in giving and guiding their children to have a religious character.